Implementation of design based learning for the development of SDGs educational games - Namita Maharjan; Kyohei Kuroda; Gunjan Silwal; Shigehiro Toyama; Yoshihiro Ominato; Yasuko Tsuchida; Nobuo Araki; Takashi Yamaguchi; Makoto Ichitsubo (OmniaScience, 2022)
Education on sustainable education (ESD) is gaining momentum to ensure that SDGs are met by 2030. The educational institutions have significant role in fostering ESD. However, there is lack of educational resources to be used for ESD. Particularly, teaching the concept of SDGs needs an attention grabbing and engaging approach and Design Based Learning (DBL) holds much potential. The main objective of this investigation was to describe the development of SDGs education resources i.e., SDGs educational games using DBL approach. Besides, the generic skills of the students during DBL were assessed during game development phase. The outputs of DBL were Bingo Mat game, Carrom board game and Sugoroku game. These games were validated for their effectiveness as resource for teaching and learning SDGs. The results revealed the positive impact on the generic skills of students through DBL during game development phase. Moreover, the response results of the players highlighted that carrom board game offered them the gaming experience while Bingo and Sugoroku offered them learning experience. Another important finding of this study is the need to teach SDGs from the younger age as the level of education had significantly impacted on their knowledge about SDGs. The results of this study will contribute to the domain of ESD by articulating an alternative pedagogy of integrating DBL with SDGs as invigorating educational resources and faculty development method.